2019
DOI: 10.1108/jamr-11-2017-0102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of GST announcement on stock market volatility: evidence from intraday data

Abstract: Purpose: The purpose of this paper is to examine the effect of GST announcements (pre and post) on Malaysian stock market index. This study also utilised intraday data to look into intraday market volatility post-GST announcement . Design/methodology/approach: Both daily closing prices and intraday data of different

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…A study using environmental variables might be interesting as these variables can affect the stock returns, and it has been recommended by Sariannidis et al (2016). According to Haron and Ayojimi (2019a), the country in which GST is implemented can see the effect, and India did so in 2017. As a response, researchers can bridge this gap.…”
Section: Research Gap Identified In the Indian Context From The Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A study using environmental variables might be interesting as these variables can affect the stock returns, and it has been recommended by Sariannidis et al (2016). According to Haron and Ayojimi (2019a), the country in which GST is implemented can see the effect, and India did so in 2017. As a response, researchers can bridge this gap.…”
Section: Research Gap Identified In the Indian Context From The Existing Literaturementioning
confidence: 99%
“…Wang (2019) found that stock market of Taiwan underperformed during the political crisis. The reaction of stock market due to announcement of goods and service tax is studied by Haron and Ayojimi (2019a, b) which shows that GST announcement made the Malaysia stock market more volatile as compared to before announcement using daily data and intraday data. Ho and Odhiambo (2019) has examined that trade openness shows positive and negative effect in the long run and short run, respectively, in Hong Kong.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…CPO price volatility can provide information on movements in the Malaysia industry growth [46]. The price interaction in the CPO market will make it easier for investors to shift their investments to other forms that are considered more profitable [47].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…It could serve as a response to address the allegations on environmental and social impacts linked to the Malaysian palm oil industry (Norhidayu et al, 2017;Majid et al, 2021). At the same time, it can help to improve their economic income and eventually alleviate their livelihood standards (Haron and Ayojimi, 2015;Faisal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%